HISTORY OF PRE-ISLAMIC GLASSES OF TURKESTAN (Scientific journal of the Fergana State University, 2026)
Glass objects have been found in more than 50 monuments dating back to the pre-Muslim period in Turkestan. 16 types of large objects were found in 23 monuments: medical containers, tableware, chemical containers, and jewelry. The remaining objects consist of beads, beaded necklaces, bracelets, and jewelry such as “eyes” for rings and earrings. 30 different shapes of beads have been found. Traces of glass production have been discovered in 9 cities of Turkestan. As a result of further systematization of research, it was proven that not only production, but also export was carried out. It was found that craftsmen began to produce luxurious dishes for everyday use and for guests, depending on the needs of the population. This article analyzes the state of glass production in Turkestan in the pre-Islamic period based on historical data.